Determining Audit Delay: The Role of CEO Expertise and Bankruptcy Prediction - LESTARI, Ni Luh Putu Ratna Wahyu; NARINDRA, Anak Agung Ngurah Mayun (PT Keberlanjutan Strategis Indonesia, 2025)
This study examines the influence of CEO Expertise and Bankruptcy Prediction on audit delay. The phenomenon of delays in the publication of audited financial reports remains a recurring problem in Indonesia, requiring a deeper study of the influencing factors. This study was conducted on consumer goods industry companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling method used was purposive sampling with certain criteria, and 33 companies were selected as samples. The data collection method was carried out by tracing and recording the necessary information in secondary data in the form of annual reports and audit reports by independent auditors. The analysis method used in this study was quantitative analysis using panel data regression methods assisted by statistical data processing programs using Eviews12. The results showed that the role of CEO expertise had a negative effect on audit delay, while bankruptcy prediction had no effect on audit delay